Radiological Manifestations of Kimura’s Disease: A Case Report - Bharadwaj Saraswathula; Shirish Vaidya; Pratap Singh Parihar; Gahana Kataria (Journal of Clinical and Diagnostic Research)
Kimura disease is a rare and non malignant soft tissue disorder characterised by asymptomatic swelling, predominantly in the craniofacial region. It is commonly associated with elevated eosinophil counts and systemic manifestations. This case study covers a 45-year-old male who presented with substantial right parotid oedema that had developed over five years. He was referred to the Radiology department for Magnetic Resonance Imaging (MRI), which revealed an enlarged superficial lobe of the right parotid gland, hypointense on T1 and hyperintense on T2/FLAIR. Multiple enlarged lymph nodes with diffusion restriction were observed at the right levels Ib, II, and III, with the largest at level II on the right-side. The bilateral lacrimal glands were prominent, with postcontrast enhancement. The postcontrast T1-weighted MRI showed tubular signal-intensity voids, likely representing fast-flowing vascular structures. When an individual of Asian descent presents with a subcutaneous mass that is either partially or poorly delineated, exhibiting high signal intensity on T1- and T2-weighted imaging, accompanied by uniform enhancement, adjacent subcutaneous oedema, and internal flow voids, it is imperative to consider Kimura’s disease, particularly in the presence of peripheral eosinophilia. This article focuses on the essential aspects of the disease and how the diagnosis is determined based on MRI results, supported by histopathologic features.